Limits on low-frequency radio emission from southern exoplanets with the Murchison Widefield Array. Issue 3 (28th November 2014) - Murphy, Tara; Bell, Martin E.; Kaplan, David L.; Gaensler, B. M.; Offringa, André R.; Lenc, Emil; Hurley-Walker, Natasha; Bernardi, G.; Bowman, J. D.; Briggs, F.; Cappallo, R. J.; Corey, B. E.; et al.
Abstract: We present the results of a survey for low-frequency radio emission from 17 known exoplanetary systems with the Murchison Widefield Array. This sample includes 13 systems that have not previously been targeted with radio observations. We detected no radio emission at 154 MHz, and put 3σ upper limits in the range 15.2–112.5 mJy on this emission. We also searched for circularly polarized emission and made no detections, obtaining 3σ upper limits in the range 3.4–49.9 mJy. These are comparable with the best low-frequency radio limits in the existing literature and translate to luminosity limits of between 1.2 × 10 14 and 1.4 × 10 17 W if the emission is assumed to be 100 per cent circularly polarized. These are the first results from a larger program to systematically search for exoplanetary emission with the MWA.